Hyperglycemia induced by intracerebroventricular choline: involvement of the sympatho-adrenal system - (:unkn) unknown (ELSEVIER SCIENCE BV, 2002)
Intracerebroventricular (i.c.v.) injection of choline (75-300 mug) produced a dose-dependent increase in blood glucose levels. Pretreatment with the nicotinic acetylcholine receptor antagonist, mecamylamine (50 mug, i.c.v.) blocked the hyperglycemia induced by choline (150 mug, i.c.v.), but the response was not affected by pre-treatment with the muscarinic acetylcholine receptor antagonist, atropine (10 mug, i.c.v.). Pre-treatment with the neuronal choline uptake inhibitor, hemicholinium-3 (20 mug, i.c.v.), attenuated the hyperglycemia induced by choline. The hyperglycemic response to choline was associated increased plasma levels of adrenaline and noradrenaline. The hyperglycemia elicited by choline was greatly attenuated by bilateral adrenalectomy, and entirely blocked by either surgical transection of the splanchnic nerves or by pre-treatment with the a-adrenoceptor antagonist, phentolamine. These data show that choline, a precursor of acetylcholine, increases blood glucose and this effect is mediated by central nicotinic acetylcholine receptor activation. An increase in sympatho-adrenal activity appears to be involved in the hyperglycemic effect of choline. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: choline; hyperglycemia; glucoregulation; syntpatho-adrenal activity; cholinergic activity, rat; HIPPOCAMPAL ACETYLCHOLINE-RELEASE; RAT CORPUS STRIATUM; CONSCIOUS RATS; REVERSES HYPOTENSION; TYROSINE-HYDROXYLASE; NERVOUS-SYSTEM; ALZHEIMERS-DISEASE; GLUCOSE INJECTIONS; INDUCED DECREASE; CDP-CHOLINE